Peran Guru dalam Mengembangkan Kurikulum dan Mengimplementasikan Kurikulum Merdeka di Sekolah Dasar - Nisa, Ani Khoirotun; Kusuma Wardani, Dwi Kartika (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
The aim of this research is to describe the role of teachers in developing curriculum and implementing an independent curriculum in elementary schools. The research method uses qualitative through a descriptive analysis approach. The data sources for this research include primary data sources including teachers, school principals, and secondary sources for this research include several documents such as articles related to the research. Data collection techniques in this research include observation, interviews and documentation. Data analysis follows the theory of Miles and Huberman by condensing data, presenting data, and drawing conclusions. The results show that teachers have a big role in student learning activities to achieve the designed learning objectives. Teachers experience the learning process directly, allowing them to correct weaknesses in learning strategies and develop a curriculum that promotes better education and keeps up with current developments. A well-planned educational curriculum will create competitive schools that can adapt to the ever-growing progress of the times.